A Methodology Based on Steganography and Cryptography to Protect Highly Secure Messages - Rasras, R. J.; AlQadi, Z. A.; Sara, M. R. A. (Engineering, Technology & Applied Science Research, 2019)
Steganography and cryptography are very important techniques used in data security to hide and secure secret messages in transmitted data. This paper will introduce, implement and test a novel methodology which can be used as a secure and highly efficient method of data hiding and data extracting. Some efficiency parameters will be experimentally obtained and compared with other existing methods parameters to prove the efficiency of the proposed methodology.